Older adults report moderately more detailed autobiographical memories - Gardner, Robert S.; Mainetti, Matteo; Ascoli, Giorgio A. (Frontiers in Psychology, 2015)
Autobiographical memory (AM) is an essential component of the human mind. Although the amount and types of subjective detail (content) that compose AMs constitute important dimensions of recall, age-related changes in memory content are not well characterized. Previously, we introduced the Cue-Recalled Autobiographical Memory test (CRAM; see http://cramtest.info), an instrument that collects subjective reports of AM content, and applied it to college-aged subjects. CRAM elicits AMs using naturalistic word-cues. Subsequently, subjects date each cued AM to a life period and count the number of remembered details from specified categories (features), e.g., temporal detail, spatial detail, persons, objects, and emotions. The current work applies CRAM to a broad range of individuals (18-78 years old) to quantify the effects of age on AM content. Subject age showed a moderately positive effect on AM content: older compared with younger adults reported ~16% more details (~25 vs. ~21 in typical AMs). This age-related increase in memory content was similarly observed for remote and recent AMs, although content declined with the age of the event among all subjects. In general, the distribution of details across features was largely consistent among younger and older adults. However, certain types of details, i.e., those related to objects and sequences of events, contributed more to the age effect on content. Altogether, this work identifies a moderate age-related feature-specific alteration in the way life events are subjectively recalled, among an otherwise stable retrieval profile.